Pension Funds in Chile: Bringing the State Back In - Anna Zabkowicz (Institute of Economic Research (IER), 2017)
The privatized and capitalized old-age insurance in Chile has recently witnessed reforms under President Bachelet which extended the social safety net as well as re-introduced publicly-administered programs on behalf of retirees. The article reviews the performance of the system up to the most recent reform and presents results of pension engineering in a systematic way in attempt to estimate the scope of change. The method relies on orderly analysis which is founded on review of the literature relevant to the subject. Bringing the state back into Chile's pension system can be viewed as a plan to subsidize total retirement benefits in order to improve the distressing rates of replacement and, in such indirect way, to support the longevity of privately-managed pension funds.
Keywords: P16; B52; 330; the political economy of pension reforms - funded pensions - solidarity benefits